Analisis Dampak Dari Diklat Peningkatan Kompetensi Pengawas Satuan Pendidikan Provinsi Sulawesi Selatan - Andi Nurochmah; Muhamad Bachtiar; Ansar Ansar (Publikasi Pendidikan, 2018)
The problem in this research is whether there is a significant impact from the training of the increase of superintendent competence of unit of education unit in South Sulawesi province ?. The purpose of the study was to obtain a picture of the significant impact of the training on increasing the competence of school unit superintendents The type of this research is quantitative descriptive, population of all superintendents of educational unit, research sample member of 50 superintendents of High School / Vocational School,, Data collected by using test, documentation. Then the data is analyzed by using N-Gain test analysis. The results showed that the training of superintendent  strengthening has contributed in developing the knowledge, attitude, and skills of school superintendents on the superintendent based on education unit. This is demonstrated by 96% of the training participants getting good and very good qualifications.